Implementasi Manajemen Pendidikan Karakter dalam Membentuk Kepribadian Islami Siswa di SMP Negeri 8 Binjai - Asyari, Gita; Hadijaya, Yusuf (Jurnal Pendidikan Madrasah, 2026)
The advancement of modern education requires the implementation of innovative, creative, and adaptive learning systems through the use of graphic-based instructional media in curriculum development. Conventional teaching methods often lead to low student participation, learning boredom, and difficulties in understanding abstract concepts due to limited visual support. This study aims to analyze the influence of graphic-based learning media on curriculum development, learning motivation, and students’ creativity. A descriptive qualitative approach was employed through literature review, observation, and analysis of educational sources related to visual media and modern curriculum development. The findings indicate that graphic media, including images, diagrams, illustrations, and infographics, contribute to improving conceptual understanding, learning concentration, critical thinking skills, and interactive learning communication. The integration of graphic media also supports student-centered learning practices. However, its effectiveness is constrained by technological limitations, teachers’ competencies in designing visual media, and differences in students’ learning characteristics.